Korean Wave Dan Imprealisme Budaya Bagi Remaja Aceh - Asmaunizar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The rise of the Korean wave phenomena that has hit teenagers has raised concerns regarding the existence of local culture and social norms of Acehnese society. This research uses qualitative methods with a descriptive approach. Data collection was carried out through interviews with teenagers who like watching Korean dramas, movies and Korean music, as well as through related literature. The study results show that the Korean wave has had a strong impact on fans of Korean dramas, movies and Korean music. Among the cultures that have started to enter and join in are in terms of clothing style, culinary, language, types and genres of music to physical appearance.